La tecnología como herramienta de aprendizaje - Rivero, Valeria Irina (2018)
In the student learning process, we will analyze the use of a Virtual Classroom as a pedagogical strategy parallel to the face-to-face work of the teacher. What is sought in the beginning, is to enhance competence in students, but we must not lose sight in fact that those responsible for strengthening these capacities, are the teachers. The new scenario of the teaching profession is a change with respect to the traditional role of teacher, since the accent is placed on paying greater attention to the student's learning.